1996
DOI: 10.1046/j.1365-2826.1996.04747.x
|View full text |Cite
|
Sign up to set email alerts
|

Signalling Pathways Mediating Secretory and Mitogenic Responses to Galanin and Pituitary Adenylate Cyclase‐Activating Polypeptide in the 235‐1 Clonal Rat Lactotroph Cell Line

Abstract: The neuropeptides galanin and pituitary adenylate cyclase-activating peptide (PACAP) have been implicated in the physiological regulation of lactotroph function. Using the 235-1 clonal lactotroph rat cell line we have studied the signalling pathways mediating the secretory and mitogenic responses to galanin and PACAP. Both peptides stimulated prolactin release to a similar maximal extent. PACAP (100 nM) stimulated an increase in the proliferation rate of 235-1 cells, but was significantly less effective than 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…Interestingly, cytolytic effects in tissues were occasionally correlated with the presence of galanin in the study. By contrast, mitogenic effects of galanin have been previously described on 235-1 clonal rat lactotroph cell (15)(16)(17). Thus, it is indeed plausible that galanin could contribute to cancer cell selection by promoting proliferation of a subset of malignant cells.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, cytolytic effects in tissues were occasionally correlated with the presence of galanin in the study. By contrast, mitogenic effects of galanin have been previously described on 235-1 clonal rat lactotroph cell (15)(16)(17). Thus, it is indeed plausible that galanin could contribute to cancer cell selection by promoting proliferation of a subset of malignant cells.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, PACAP stimulates the catalytic and regulatory subunits of PKA in the mouse gonadotrope ␣T3-1 cell line (Garrel et al, 1997) and inhibits TGF-␤-induced apoptosis in the human pituitary adenoma cell line HP75 (Oka et al, 1999). In the lactotrope 235-1 cell line, PACAP stimulates prolactin release through activation of the PLC pathway and exerts mitogenic effects (Hammond et al, 1996). In the lactotrope/somatotrope GH3 cell lines, nanomolar concentrations of PACAP stimulate GH and PRL release through activation of type II receptors and recruitment of voltage-gated sodium channels (Propato-Mussafiri et al, 1992;Murakami et al, 1995).…”
Section: Effects Of Pituitary Adenylate Cyclase-activating Polypepmentioning
confidence: 99%
“…It was also reported that PACAP at a concentration of a picomolar range increased PRL mRNA level independently of the cAMP/PKA pathway [33]. In the lactotroph 235-1 cell line, PACAP stimulates PRL release through activation of the PLC pathway and exerts mitogenic effects [34]. in rat somatotrophs [35].…”
Section: Introductionmentioning
confidence: 94%